Effect of tool length on plain turning performance - Ibrahim, Norfaizem (2010)
The purpose of this research paper is to find a correlation between surface roughness and cutting conditions (cutting speed, feed rate, depth of cut, and tool overhang) especially tool overhang as the output response variable in turning Aluminum Alloy 6061 without using supported (tailstock) and in dry cutting (without coolant). The tool length variable is introduced because to investigate that the vibration generated by varying the tool length could affect the resulting surface finish. Dry cutting (without using cutting fluid) are conducted to stimulate a good turning, provide a clean environment to obtain undisturbed clear cutting vibration, which result in more accurate and clear correlation between cutting condition and surface roughness. Examine the relationship that exists between the length, at a specific diameter, and surface roughness of bar stock in unsupported turning operations in an attempt to reduce setup waste in turning operations. The concept of Design of Experiments (DOE) was used for necessary experimentation. The experimental results were analyzed statistically to study the influence of process parameters on surface roughness. Response surface methodology (RSM) was used for modeling and analysis in applications where a response of interest is influenced by several variables and the objective is to optimize this response under the range of cutting condition been set. The analysis of variance revealed in this study is that feed rate, cutting speed and tool length have significance effects on the surface roughness and the best surface roughness condition is achieved at a low feed rate 0.07 mm/rev, high cutting speed 280 m/min and short tool length 22 mm. The results also show that the feed rate has big effect on surface roughness followed by tool overhang and cutting speed. The depth of cut has not a significant effect on surface roughness in this study.